2019
DOI: 10.3389/fcomm.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relationship Goal on Linguistic Behavior in Online Dating Profiles: A Multi-Method Approach

Abstract: This study uses two methods to examine whether online daters looking for a long-term relationship behave linguistically different in their profile texts compared to daters seeking casual relationships. To investigate these linguistic differences, 12,310 existing Dutch dating profiles were analyzed using the Linguistic Inquiry and Word Count (LIWC) program and a word-based classifier. Results of both methods suggest there are reliable differences in the linguistic behavior long-term and casual relationship seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Moreover, self-disclosure statements in profiles deemed more original also appeared to be more concrete compared to less original profiles, which means revealing personal information that activates detailed (image-based) representations of objects or events [ 62 ] (e.g., “Food is essential for me” vs. “Coffee and a cracker with cheese or jam are essential in my morning ritual”). As additional features of self-disclosure, we decided to take into account the number of words and the percentage of I-references, which are also associated with self-disclosure [ 63 , 64 ], as well as article use, which is seen as another measure of language concreteness [ 65 ]. A total of six self-disclosure features is thus added to the codebook.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, self-disclosure statements in profiles deemed more original also appeared to be more concrete compared to less original profiles, which means revealing personal information that activates detailed (image-based) representations of objects or events [ 62 ] (e.g., “Food is essential for me” vs. “Coffee and a cracker with cheese or jam are essential in my morning ritual”). As additional features of self-disclosure, we decided to take into account the number of words and the percentage of I-references, which are also associated with self-disclosure [ 63 , 64 ], as well as article use, which is seen as another measure of language concreteness [ 65 ]. A total of six self-disclosure features is thus added to the codebook.…”
Section: Methodsmentioning
confidence: 99%
“…Kubany et al (1995) demonstrated I pronouns increased partner sympathy and were linked to increased partner perceived closeness (Robinson et al, 2020). The use of I pronouns is indicative of a desire for a long-term relationship (van der Zanden et al, 2019). Yet, younger individuals and women are more likely to use the I pronoun (Davis & Fingerman, 2016); so, this could reflect demographic associations.…”
Section: Pronouns and Couple Dynamicsmentioning
confidence: 99%
“…Recent research on language used within online dating profiles has focused on how factors such as dating goals influence how daters present themselves in their self-descriptions. For example, online daters looking for a long-term (vs. short-term) relationship tend to provide more personal information about themselves, mention personality traits and qualities more often, and use more "I" related words within their profiles (van der Zanden et al, 2019). Online daters hoping to deceive others in their self-representations tend to write shorter self-descriptions, make fewer self-references, use fewer negative emotion words, and use more negation words (Toma & Hancock, 2010).…”
Section: Language Use In Online Datingmentioning
confidence: 99%